Implementasi Metode Analytic Hierarchy Process (AHP) dalam Sistem Rekomendasi Mitigasi Bencana Alam - Nugraha, Nur Budi; Santosa, Yaqutina Marjani; Puspaningrum, Alifia; Saiful, Ibnu (Journal of Computer System and Informatics (JoSYC), 2024)
Flood disasters are a serious threat faced by various regions in Indonesia, including Indramayu Regency, West Java, as one of the most vulnerable areas. The geographical characteristics of Indramayu, which are dominated by lowlands and surrounded by large rivers such as Cimanuk and Cipunagara, cause this area to experience annual flooding, especially during the rainy season. The impact of this disaster extends from material losses to significant social and economic disruption for local communities. This research aims to develop an effective and targeted flood disaster mitigation recommendation system. Using a quantitative approach, this study focuses on developing a system based on the Analytical Hierarchy Process (AHP) method. The research methodology includes several key stages. First, identify and determine criteria and sub-criteria that are relevant to flood disaster mitigation. Second, weighting criteria using pairwise comparisons. Third, consistency calculations to ensure the validity of the assessment. Finally, the construction of a decision hierarchy that integrates all analysis elements. The results of the AHP analysis are then integrated into a system specifically designed to support decision making in disaster mitigation. The system combines geographic, demographic and historical disaster data to provide comprehensive and contextual recommendations. The system being developed is expected to facilitate several key aspects of disaster management in terms of quick and effective decision making by the authorities, increasing public awareness and knowledge about disaster management and understanding disaster distribution patterns.